Developing a mobile decision support system for monitoring child growth from 0 to 23 month of age - Fungo, Debora (Mzumbe University, 2023)
A dissertation submitted in partial fulfillment of the requirements for the award of the Degree of Masters of Science (Information Technology and Systems) Mzumbe University